Implementation of a two-factor authentication system for mobile phones - Leopando, Jonathan L.
For many years, passwords have served as the primary means of authentication for users on the Internet. The increased growth of the latter has meant that users are having to use passwords with greater frequency than ever before. However, in recent years it has been recognized that in the face of greater security threats, passwords are no longer an adequate means of authentication. Increasingly, what is known as two-factor authentication methods are growing in popularity. Most two-factor authentication methods use a separate piece of hardware to serve as the second factor. This has certain disadvantages. In this paper, we discuss two-factor authentication using an item of hardware that is common, readily available, and almost always carried by people today: the mobile phone.